2015
DOI: 10.1080/19440049.2015.1087651
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizidine and tropane alkaloids in teas and the herbal teas peppermint, rooibos and chamomile in the Israeli market

Abstract: Dehydro pyrrolizidine alkaloids (dehydro PAs) are carcinogenic phytotoxins prevalent in the Boraginaceae, Asteraceae and Fabaceae families. Dehydro PAs enter the food and feed chain by co-harvesting of crops intended for human and animal consumption as well as by carry-over into animal-based products such as milk, eggs and honey. Recently the occurrence of dehydro PAs in teas and herbal teas has gained increasing attention from the EU, due to the high levels of dehydro PAs found in commercially available teas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…In recent years, several studies have demonstrated that a real danger is posed by Pyz alks extracted from herbs in teas and infusions . In line with previous studies, our study confirmed the migration of Pyz alks from herbs to water infusions, albeit at a lower rate compared to the potential content.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In recent years, several studies have demonstrated that a real danger is posed by Pyz alks extracted from herbs in teas and infusions . In line with previous studies, our study confirmed the migration of Pyz alks from herbs to water infusions, albeit at a lower rate compared to the potential content.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, it should be emphasised that in general, people consume no more than one/two cups of herb tea/infusions per day, and that several other foods may also contain alks. As regards Pyzs, the most widely studied alks, commodities such as honey, cereals, milk, and green salads could also definitely affect our daily intake …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations